Investigating the effectiveness of flipped learning on enhancing students’ English language skills - Hadeel Abu Safiyeh; Mohammed Farrah (University of Kuningan, 2020)
This study aimed at investigating the effectiveness of utilizing flipped classrooms on seventh graders' English language skills (reading comprehension, writing, listening, and speaking) and areas (grammar and vocabulary) at Farahat Secondary Girls' School. The researchers chose two 7th classes for the study, and then the flipped learning was implemented with the experimental group, while the control group had traditional learning. According to data collection, the researchers used a pretest and a posttest to measure the students' achievements after 9 weeks of flipping the classrooms, which were executed on 36 female students. Then, a semi-structured interview was conducted to draw a clear picture of flipped learning. The major findings of the study revealed that there were significant differences in English language skills and areas between both groups. The experimental group achieved higher scores than the control one, and the most prominent improved skills are listening, speaking, and communication.